TNF-alpha expression in trypanosomiasis resistant and susceptible mouse strains during infection with Trypanosoma congolense - Iraqi, F.A.; Sileghem, M.R.; Teale, A.J. (OAU/STRC, 2001)
In previous studies, the resistance to infection by Trypanosoma congolense has been localized in a region of chromosome 17 consisting the gene of TNF alpha. On the other hand, it has been Reported that the TNF alpha has a trypanolitic activity. So, we have started to study the expression of TN alpha at the protein level as well as at the level of the mANR, with resistant mice or susceptible strain infected by trypanosomes, comparing with non-infected witness mice. Mice with two resistant strain (C57BL/6 and of two susceptible strains AJ and BALB/c) have been under infection by T. congolense IL 1140 with the help of an infection of infected tsetse flies (Glossina morsitans Centralis). The same number of mice of each strain became under the ordeal of non-infected tsetse flies. Cells from four different sources 1) pooled branchial/inguinal/auxillary lymph nodes 2) mesenteric lymph node 3) spleen and 4) peritoneal cavity were collected at days 4, 7, 17, 21 and 28 post-infection and four days pre-infection. At each collection, cells of four infected and four uninfected mice were pooled and allocated for TNF alpha bioassay and for mARN. The quantification of mARN has been realized by amplification in chain by polymerase chain reaction products reverse of (RT-PCR) messengers using the B-actine like as internal witness. In the ganglions, of day 7 post-infection, the bioassay has shown a reaction 50 times higher in TNF alpha in expression at the protein with resistant strains compared to a susceptible strain. A more important reaction was observed in the splenic cells of resistant strains, but for each strain, the reaction is weaker than the ganglion\92s. At day 14 post-infection, the TNF alpha expression at the protein was weaker than at the higher level observed at day 7 post-infection with resistant strains. The reactions have increased at day 14 and 21 with susceptible strains, but without earlier getting closer to the observed levels, in the infection of resistant strains. On the other hand, the quantification by the RT-PCR of mARN of TNF alpha shows a reduced quantity of messengers in the resistant strains, and more important with susceptible strains at the premature stage. These results can be explained by a substantial increase of messengers translation of TNF alpha pre-existing in resistant strains during the first peak of parasitism. This takes place but more slowly and in a less important way in susceptible strains.